2014
DOI: 10.1111/hepr.12351
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of liraglutide effects in non‐alcoholic steatohepatitis and non‐alcoholic fatty liver disease with glucose intolerance in Japanese patients (LEANJ)

Abstract: Our pilot study demonstrated that treatment with liraglutide had a good safety profile and significantly improved liver function and histological features in NASH patients with glucose intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(182 citation statements)
references
References 54 publications
9
171
0
2
Order By: Relevance
“…This effect appears to be mediated by its action on weight loss [42] . Similar results were also found in another study of NASH patients, and liraglutide therapy significantly improved their body mass index, visceral fat accumulation, aminotransferases, glucose abnormalities and histological features [43] . However, another study found that GLP-1 agonists treatment with exenatide or liraglutide for 6 months in patients with T2DM dramatically improves hepatic steatosis measured by using 1 H MRS; however, the change did not correlate with changes in body weight and abdominal fat, but it did correlate with reduction in HbA1c [44] .…”
Section: Human Clinical Studiessupporting
confidence: 86%
“…This effect appears to be mediated by its action on weight loss [42] . Similar results were also found in another study of NASH patients, and liraglutide therapy significantly improved their body mass index, visceral fat accumulation, aminotransferases, glucose abnormalities and histological features [43] . However, another study found that GLP-1 agonists treatment with exenatide or liraglutide for 6 months in patients with T2DM dramatically improves hepatic steatosis measured by using 1 H MRS; however, the change did not correlate with changes in body weight and abdominal fat, but it did correlate with reduction in HbA1c [44] .…”
Section: Human Clinical Studiessupporting
confidence: 86%
“…Furthermore, a few data support a beneficial impact of liraglutide on liver inflammation markers in NAFLD patients with T2DM [67] , in obese women with polycystic ovary syndrome and NAFLD [68] and in one T2DM patient with concomitant cryptogenic cirrhosis [69] . In a recent pilot Japanese study, treatment with liraglutide had a good safety profile and significantly improved liver function and histological features in NASH patients with glucose intolerance [70] . A clinical case of suspected liraglutide-induced autoimmune hepatitis has been recently reported [71] .…”
Section: Hepatic Safetymentioning
confidence: 99%
“…3L). These results suggest that E6 may be useful for the treatment of fatty liver diseases such as nonalcoholic fatty liver disease and nonalcoholic steatohepatitis (44,45). Given the very high potency, the relatively long serum half-life, and the necessity of parenteral administration, E6 is an ideal candidate for microstructure array (MSA)-based transdermal delivery.…”
Section: Resultsmentioning
confidence: 99%